Gender differences in traditional Chinese medicine use among adults in Taiwan. - Chun-Chuan Shih (Public Library of Science (PLoS), 2012)
Objectives The increasing use of complementary, alternative medicine (CAM) and traditional Chinese medicine (TCM) has attracted attention. We report on the gender difference in TCM use among the general population in Taiwan in a population-based, cross-sectional study. Methods We collected data on socio-demographic factors, lifestyle and health behavior from the 2001 Taiwan National Health Interview Survey. The medical records of interviewees aged 20-69 years were obtained from National Health Insurance claims data with informed consent. The prevalence of TCM use and the average frequency of TCM use were compared between women and men. Results Among 14,064 eligible participants, the one-year prevalence of TCM use for women and men was 31.8% and 22.4%, respectively. Compared with men, women had a higher average TCM use frequency (1.55 visits vs. 1.04 visits, p<0.001). This significant difference remained evident after excluding gender-specific diseases (1.43 visits vs. 1.03 visits, p<0.001). The average TCM use frequency was significantly higher in women than in men across all age groups. TCM use correlates differed for women and men. Marital status (odds ratio [OR] = 1.55, 95% confidence interval [CI] = 1.30-1.85), family income and unhealthy lifestyle (OR = 1.50, 95% CI = 1.30-1.74) were factors associated with TCM use in men but not in women. Conclusions In Taiwan, women used more TCM services than men and the gender differences in the TCM use profile persisted across age groups.